Hungry Heartland: College Students - Howard, Bridget; Jaeger, Natalie; Yu, Han; Joglekar, Shreepad; Hallaq, Tom G. (Kansas State University, 2018)
Kansas State University is only one of many college campuses in a food desert. Student on limited incomes and often without reliable transportation can find themselves with limited access to unprocessed food. When Sophia Doss came to K-State from California, she had no idea she would face challenges of getting fresh food for a meal.
Keywords: food deserts; urban communities; college students